Ubuntu philosophy as a humanistic–existential framework for the fight against the COVID-19 pandemic - Chigangaidze, Robert Kudakwashe; Matanga, Anesu Aggrey; Katsuro, Tafadzwa Roniah (SAGE Journals, 2022)
Ubuntu has been identified by several scholars as a philosophy that provides a framework to fight health disasters such as COVID-19. Ubuntu refers to the African worldview of seeing oneself through others. It refers to the pattern of interconnectedness between people in the form of a philosophy or worldview. Ubuntu explores concerns about cosmic and global context of life. This article stipulates that Ubuntu can provide ways to deal with challenges that emerge with the COVID-19 pandemic. Ubuntu fosters the integrated components of humanity as it appreciates the biological, psychosocial, spiritual, and environmental aspects of life. The article explores several themes such as self-awareness and societal responsibility, holism, spirituality, health promotion, food security, social justice and human rights, generosity, sharing, and teamwork. Others have advanced that Ubuntu is a philosophy to adopt in the fight against epidemics, and we seek to broaden the debate by exploring Ubuntu axiological and ontological humanistic–existential themes. Finally, the article calls for the adoption of Ubuntu philosophy in psychological and social work interventions in the fight against the COVID-19 pandemic.